2016
DOI: 10.1542/peds.2015-2851n
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Transition Services for Youth With Autism Spectrum Disorders: Perspectives of Caregivers

Abstract: BACKGROUND AND OBJECTIVE: This paper seeks to describe the experience of youth with autism spectrum disorder (ASD) in making the health care transition (HCT) to adult care. METHODS:We surveyed 183 parents and guardians of youth with ASD, assessing the extent to which youth and families experienced and desired HCT services, their satisfaction with services, and obstacles to transition. Descriptive statistics were used to examine HCT measures and Fisher's exact and t tests assessed whether demographic or health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 36 publications
3
44
1
Order By: Relevance
“…This time commitment is also a burden to families (van Tongerloo et al, ). Nonetheless, they still experience unmet needs, despite their higher rate of utilization, greater expenditure, and longer time spent in medical appointments (Cheak‐Zamora & Farmer, ; Kogan et al, ; Kuhlthau et al, ; Strunk et al, ; Williams et al, ; Zuckerman et al, ). Although having a medical home is associated with fewer unmet needs (Cheak‐Zamora & Teti, ; Kogan et al, ) and greater satisfaction with care (Zuckerman et al, ), most children with ASD do not have medical homes (Williams et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This time commitment is also a burden to families (van Tongerloo et al, ). Nonetheless, they still experience unmet needs, despite their higher rate of utilization, greater expenditure, and longer time spent in medical appointments (Cheak‐Zamora & Farmer, ; Kogan et al, ; Kuhlthau et al, ; Strunk et al, ; Williams et al, ; Zuckerman et al, ). Although having a medical home is associated with fewer unmet needs (Cheak‐Zamora & Teti, ; Kogan et al, ) and greater satisfaction with care (Zuckerman et al, ), most children with ASD do not have medical homes (Williams et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these challenges, parents report that they are satisfied overall with their child's care on measures of parent satisfaction. One large study (n = 2,088) by Chiri and Warfield (2012) found that only 7.9% of caregivers were dissatisfied with their child's general health care, and another study found that only 3.2% of parents were dissatisfied with their child's transition services (Kuhlthau et al, 2016). Higher levels of satisfaction are associated with receiving care in a medical home (Golnik, Maccabee-Ryaboy, et al, 2012).…”
Section: Parent Satisfaction With Carementioning
confidence: 99%
“…6 epilepsy, and behavioral/psychiatric conditions, 7,8 among the most promising and important areas, along with understanding more about adolescence and the transition to adulthood with ASD. 9,10 Some network studies have addressed quality of life, health services, and health economic issues, which are areas that merit more attention and investment. 11,12 Nonetheless, it remains clear that there is much more to do to understand clinical conditions among children with ASD and to improve the underlying science needed to inform treatment choices.…”
Section: Current Networkmentioning
confidence: 99%
“…31,32 A survey of 183 parents and guardians of youth with autism spectrum disorders revealed that only 60% received transition services, despite high rates of insured status and access to health care. 33 The greatest impediments in this population included reported lack of information regarding the transition process and difficulty finding an adult primary care clinician with sufficient knowledge of autism spectrum disorder. 33 A convenience sample survey of 155 transitioning patients with various childhood chronic diseases and 104 parents reported that significant gaps in transition education existed regarding a variety of health-related and future vocational issues.…”
mentioning
confidence: 99%
“…33 The greatest impediments in this population included reported lack of information regarding the transition process and difficulty finding an adult primary care clinician with sufficient knowledge of autism spectrum disorder. 33 A convenience sample survey of 155 transitioning patients with various childhood chronic diseases and 104 parents reported that significant gaps in transition education existed regarding a variety of health-related and future vocational issues. 32 This report also cited lack of adult specialist providers as a barrier to transition.…”
mentioning
confidence: 99%